Manejo de las excretas de cerdos y las alternativas de mitigación al impacto ambiental - Fuentes Bustamante, Geomara Lilibeth (2020)
A documentary research was carried out with the aim of generating information on solutions to environmental contamination problems caused by pig excreta. The research was of a bibliographic documentary type by the inductive deductive method, it was prepared based on the collection and review of scientific articles and books published on the web, on issues related to the environmental impact produced by pig excreta. The collection of information was carried out between the months of July and September 2020. This bibliographic research allowed to demonstrate the development of many methods of treatment of pig excreta, to try to reduce its polluting value and mitigate the negative effects on health. public. Among them are modifying the diet, in such a way that the animals consume the necessary nutrients according to their nutritional requirements in each stage, addition of phytases in the diet to increase phosphorus efficiency and thus decrease total phosphorus and consequently decrease excretion. phosphorus to the environment. In the same way, the treatments to the excreta can be carried out by adding exogenous enzymes that reduce the generation of ammonia from the excreta (and corrosion), as well as the use of bioreactors, biodigesters, use of deep bed, etc., which in They generally have the purpose of reducing the load of pollutants present in the excreta and thus being able to use them either in agriculture or as a food resource for other animals.